Evaluation of Two-Wheel Tractor Fuel Consumption Rates During Direct Seeding of Sorghum and Pearl Millet in Sandy and Clayey Soils - Tinashe Madzivanzira; Brighton M. Mvumi; Raymond M. Nazare; Elijah Nyakudya; Florence Mtambanengwe; Paul Mapfumo (Advances in Agriculture)
Knowledge on the fuel consumption of agricultural tractors helps in the management and planning of farm operations. Fuel consumption data are also important in calculating the cost of using machinery to carry out operations and to estimate the contribution of agricultural machinery to greenhouse gas emissions. Various factors, including operating speed, soil type and tractor load affect the fuel consumption rate. Promotion of two-wheel tractors (2WTs) as an appropriate power-source for smallholder farmers has been on the rise in Zimbabwe. However, the fuel consumption performance of these tractors for some operations has not been established. Our study focused on evaluating the fuel consumption performance of a 2WT–based direct seeding system for sorghum and pearl millet crops in clayey and sandy soils at varying speeds of operation. Results showed that crop type, soil type and speed of operation affect fuel consumption rate. Increasing the operating speed resulted in a decrease in fuel consumption rate. For the same soil type, the fuel consumption rates for pearl millet seeding were higher than those of planting sorghum. At the recommended planting speeds, the fuel consumption rates when planting sorghum were 6.42 L/ha and 7.34 L/ha for clayey and sandy soils, respectively. For pearl millet planting, the fuel consumption rates were 10.93 L/ha and 11.90 L/ha for clayey and sandy soils, respectively. This information on fuel consumption rate can be used by farmers and other operators of 2WTs for planning the fuel quantity and budgetary requirements.